Inventory of parasitoids for a biological control of fruits flies (Diptera: Tephritidae) in Côte d’Ivoire - Hervé K. Koua; EAAB, Kadio; LRN, Aboua; PB, Seri-Kouassi; N, Hala; JF, Vayssières (Journal of Research in Biology, 2011)
Flies are major pests of fruits in Côte d’Ivoire. The fight against these pests is achieved by using several methods including parasitoids. The study was carried out under orchards semi naturel conditions in southern, central, northern areas of Côte d’Ivoire. An inventory was made after a mass breeding in box containing fruits placed in sterilized and humidified sand. The fruits were covered by muslin. Four species of fly hosts of the parasitoids were listed: Bactrocera invadens, Ceratitis quinaria, Ceratitis cosyra and Dacus bivittatus. Eight species of parasitoids belonging to the Hymenoptera order, Braconidae family and three genera were identified: Diachasmimorpha(D.) tryoni, D. fullawayi, Fopius(F.) arisanus, F. caudatus, F. vandenboschi, F. silvestrii, Psyttalia (P)lounsburyi and P. incisi. The most abundant species were D. tryoni, D. fullawayi, F. arisanus and F. Caudatus. Fruits infested by females of B. invadens and C. cosyra were presented to females of the four parasitoids species. The parasitism rates varied from 26.36 ± 0.31 to 48.95 ± 0.71% on B. invadens and 34.33 ± 0.39 to 52.47 ± 0.33 % on C. cosyra. The highest parasitism rates were recorded with D. tryoni on the two hosts. The species D. tryoni seems to be the best parasitoid to control the populations of fruits flies in Côte d’Ivoire